2020
DOI: 10.1097/icl.0000000000000766
|View full text |Cite
|
Sign up to set email alerts
|

Scleral Lens Visual Rehabilitation of Sequential Bilateral Corneal Hydrops With Post-LASIK Ectasia

Abstract: This case report describes a unique presentation of bilateral sequential acute corneal hydrops that manifested several years after laser in situ keratomileusis. Initial management included anterior chamber perfluoropropane gas injection and corneal suturing. Longer-term visual rehabilitation involved the use of scleral lenses which significantly reduced lowerand higher-order ocular aberrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Severe keratoconus may result in corneal hydrops, characterised by marked corneal oedema due to a break in the posterior limiting lamina, which allows aqueous to enter the corneal stroma and epithelium. Although hydrops can be selflimiting within ~3 months, acute cases may require corneal suturing or intracameral gas injection depending upon the severity [149]. Corneal hydrops can results in central vision-impairing scar tissue and corneal irregularity, necessitating in many cases the need for scleral contact lenses to achieve functional vision [150], and in some cases corneal transplantation [84].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Severe keratoconus may result in corneal hydrops, characterised by marked corneal oedema due to a break in the posterior limiting lamina, which allows aqueous to enter the corneal stroma and epithelium. Although hydrops can be selflimiting within ~3 months, acute cases may require corneal suturing or intracameral gas injection depending upon the severity [149]. Corneal hydrops can results in central vision-impairing scar tissue and corneal irregularity, necessitating in many cases the need for scleral contact lenses to achieve functional vision [150], and in some cases corneal transplantation [84].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…24 Although not included in the results of this review, there are also some case reports, such as the one published by Kumar et al that support this position. 37 It should be noted that in their study, Woodward et al describe 20% of failure rate with RGPCL in patients with postoperative ectasia, such as discomfort and intolerance to lens wear, inability to fit the shape of the ectatic cornea properly, or poor visual acuity with lenses. 36…”
Section: Corneal Ectasia After Refractive Surgerymentioning
confidence: 89%
“…Although they are not included in this review, it is worth mentioning that there are many case reports that support these results. 37,38,[48][49][50] Several authors have shown a decrease in OSDI and an improvement in the NEI-VFQ-25 questionnaire in these patients after CL adaptation 8,44,47,49,51 In this regard, Tougeron-Brousseau et al reported how the adaptation of SL influences patients' visionassociated quality of life. They reported that 92% of their patients were successfully adapted, all of them showing an improvement in OSDI and in NEI VFQ-25, with an average value that went from 76.9 to 37.1 in the former and an improvement from 25.1 to 67.4 in the last, after CL adaptation.…”
Section: Severe Ocular Dryness and Ocular Surface Diseasesmentioning
confidence: 92%
See 2 more Smart Citations